Privacy and power: a transatlantic dialogue in the shadow of the NSA-Affair - Miller, Russell A. (Cambridge University Press, 2017)
Foucault's panopticon : a model for NSA surveillance? / Sarah Horowitz -- A rose by any other name? the comparative law of the NSA-Affair / Russell Miller -- Privacy as a public good / Joshua Fairfield and Christoph Engel -- The right to data protection : a no right thesis / Ralf Poscher -- Privacy, rechtsstaatlichkeit, and the legal limits on extraterritorial surveillance / Anne Peters -- Privacy, hypocrisy, and a defense of surveillance / Benjamin Wittes -- Sensing disturbances in the force : unofficial reflections on developments and challenges in the U.S.-Germany security relationship / Ronald Lee -- Metadeath : how does metadata surveillance inform lethal consequences? / Margaret Hu -- Reframing E.U. responses to criminal unauthorized disclosures of U.S. intelligence activities / Andrew Borene -- Fourth Amendment Rights for Nonresident Aliens / Alec Walen -- Forget about it? harmonizing European and American protections for privacy, free speech, and due process / Dawn Nunziato -- The challenge of limiting intelligence agencies' mass surveillance regimes : why western democracies cannot give-up on communication privacy / Konstantin von Notz -- German exceptionalism? the debate about the German foreign intelligence service (BND) / Stefan Heumann -- Structural reform of intelligence agencies' involvement in criminal investigations? / Marc Engelhart -- Legal restraints on the extraterritorial activities of Germany's intelligence services / Klaus Gärditz -- Assessing the CJEU's "google decision" : a tentative first approach / Johannes Masing -- Towards multilateral standards for foreign surveillance reform / Ian Brown, Morton H. Halperin, Ben Hayes, Ben Scott & Mathias Vermeulen -- Espionage, security interests, and human rights in the second machine age : NSA mass surveillance and the framework of public international law / Silja Voeneky -- The need for an institutionalized and transparent set of domestic legal rules governing transnational intelligence-sharing in democratic societies / Susana Sanchez Ferro -- Developments in European data-protection law in the shadow of the NSA-Affair / Jens-Peter Scheider -- Why blanket surveillance is no security blanket : data retention in the UK after the European data-retention directive / Lucia Zedner -- Do androids forget European sheep? : the CJEU's concept of a "right to be forgotten" and the German perspective / Bernd Holznagel & Sarah Hartmann -- Adequate transatlantic data exchange in the shadow of the NSA-Affair / Els De Busser -- The intimacy of Stasi surveillance, the NSA-Affair, and contemporary German cinema / Laura Heins -- Hans Fallada, the Nazis, and the defense of privacy / Roger Crockett -- Watching the Mass Ornament with Dr. Mabuse / Summer Renault-Steele -- Secrecy, surveillance, spy fiction : myth-making and the misunderstanding of trust in the transatlantic intelligence relationship / Eva Jobs -- CITIZENME : what Laura Poitras got wrong about the NSA-Affair / Russell Miller & Stephen Chovanec